Signature of pre-pregnancy microbiome in infertile women undergoing frozen embryo transfer with gestational diabetes mellitus - Wenzheng Guan; Tian Zhou; Jiao Jiao; Liwen Xiao; Zhen Wang; Siyuan Liu; Fujie Yan; Fangqing Zhao; Xiuxia Wang (npj Biofilms and Microbiomes)
Abstract This study aims to evaluate differences in gut microbiota structures between infertile women undergoing frozen embryo transfer (FET) with gestational diabetes mellitus (GDM) and healthy controls (HCs), and to identify potential markers. We comprehensively enrolled 193 infertile women undergoing FET (discovery cohort: 38 HCs and 31 GDM; validation cohort: 85 HCs and 39 GDM). Gut microbial profiles of the discovery cohort were investigated during the pre-pregnancy (Pre), first trimester (T1), and second trimester (T2). The microbial community in the HCs group remained relatively stable throughout the pregnancy, while the microbial structure alteration occurred in the GDM group during T2. A model based on ten bacteria and ten metabolites simultaneously was used to predict the risk of GDM developing in the pre-pregnancy state with the ROC value of 0.712. Algorithms on the basis of marker species and biochemical parameters can be used as effective tools for GDM risk evaluation before pregnancy.